Life cycle inventory of polyethylene glycol-modified lignin and greenhouse gas emission reduction by replacing existing resins - Yuki Fuchigami; Yasunori Ohashi; Eri Takata; Tatsuhiko Yamada (Journal of Wood Science)
Abstract This study investigated the greenhouse gas (GHG) emissions of polyethylene glycol-modified lignin (PEG-modified lignin) from the raw material procurement stage to the production stage based on the production process of PEG-modified lignin in a commercial-scale plant and analyzed the GHG emission reduction by replacing resins derived from fossil resources. The GHG emissions of the PEG-modified lignin were 0.85 kg-CO2e/kg. The establishment of a process to recover and recycle used PEG in the product manufacturing process and reduce the input of virgin PEG has a significant impact on reducing GHG emissions. Furthermore, in the production of a masterbatch of PEG-modified lignin mixed with nylon (PA6), GHG emissions were reduced with an increase in PEG-modified lignin content, with reductions of approximately 14 and 36% for the PEG-modified lignin content of 20 and 50%, respectively. This indicates that PEG-modified lignin has the potential to contribute to GHG reduction as an alternative to fossil fuel resources.